Analysis and Prediction of the State of Road Accidents and Traffic Crimes in the Republic of Kazakhstan - BAKISHEV, Kairat A.; BASHIROV, Aleksander V.; FETKULOV, Alikjan K. (Journal of Advanced Research in Law and Economics, 2018)
In the article the author addresses an important problem on a global scale that modern society faces – that of ensuring road safety. Despite the decline in road traffic accidents in the country in recent years, they are still quite widespread, having a noticeable negative impact on civilized development and public safety in the world. With increasing vehicle numbers, the intensity and speed of traffic flows and owing to careless behavior of road users, accidents and catastrophes are increasingly occurring, resulting in death and injury to people. In Kazakhstan more than 2,000 people die and over 17,000 are injured in road accidents every year. Therefore, the fight against violations of traffic rules should be among the main objectives of the criminal policy of the state. The author points out that a number of targeted traffic safety programs, aimed at reducing the accident rate of transport and the severity of its consequences in the country, have not yielded tangible and stable results. The reason for this is the lack of adequate and complete understanding of the real causes and conditions of road traffic offences. To develop effective measures to ensure road safety, it is necessary to analyze the statistical data on the accident rate of motor vehicles in the past and in the present, as well as a forecast of its possible changes and trends in the future. To do this, the work investigated the statistical fluctuations in road accidents and traffic crimes between 1991 and 2016, and analyzed the data on victims of road accidents, social and transport risks. The author emphasizes that it is possible to significantly affect the level of road accidents, and significantly reduce human and material losses only by consistently bringing the institutional environment of the road to standards that are comparable to the developed countries of the world. To solve this problem, a number of specific measures have been proposed.